Actor groups influencing and shaping sustainable microalgae value chains in Europe - Schrammel, Maria; Seebacher, Lisa M.; Feichtinger, Judith (Frontiers in Aquaculture, 2023)
Microalgae are an evolving field to produce sustainable nutritious food with low environmental impact. To shape the emerging European value chain in a sustainable way, all actors and processes need to be considered. This article builds on the results of multi-stakeholder scenario workshops organised within the EC-H2020-funded project ProFuture. It investigates the roles different actors along the microalgae value chain hold to shape it. A qualitative analysis identified three actor groups: (1) microalgae producers and processors, and researchers who work with microalgae and their development, (2) policy makers, and large industrial players, who influence the political and economic possibilities of the microalgae value chain and (3) consumers, who play a key role in order to root sustainable microalgae food products in the market. The paper shows how these groups interlink and draws conclusions about their roles for shaping the European microalgae value chain.